Estratégias de leitura para o gênero charge - Silva, Karine Tiepo da (2019)
This dissertation, connected to the Postgraduate Program in Literature of the University of Passo Fundo, in the line of research Reading and Formation of Reader, aims on the study of reading strategies related to newspaper cartoons. Thus, the main goal of this dissertation is to understand the reading strategies implied in the process of understanding the newspaper cartoons; and the specific objectives are as follows: a) to understand basic reading strategies and how to work with them in the classroom; b) identify reading strategies focused on syncretic texts; c) understand the specificities of the genre newspaper cartoon and whether it requires differentiated reading strategies; and d) to point out reading strategies aimed at the understanding / interpretation of this discursive genre. The corpus is constituted by a cartoon that was published in the Zero Hora newspaper, in 2018. The analysis is based in studies of reading strategies and discursive semiotics. The choice of this approach is justified by the fact that we believe that the articulation between two theories may enrich the analysis, insofar as the theoretical presuppositions of both do not oppose, but complement each other. The theoretical basis, as far as the discursive semiotic theory is concerned, occurs essentially in Greimas and Courtés (2013), Fiorin (2016), Barros (2005, 2012) and Teixeira, Faria & Souza (2014). We also approached the issues of interdiscursivity/dialogism and textual genre based on Bakhtin (2016), Fiorin (2006) and Marcuschi (2008). As for reading strategies, we based our work on Solé (1998), Harvey & Goudvis (2007), Kleiman (1995, 2008) and Girotto & Souza (2010). As fr the methodological procedures, this corresponds to a descriptive research of bibliographic character, applied nature and qualitative approach. The analysis indicates that the understanding of cartoons requires, above all, the activation of previous knowledges related to the objective or the social function of the genre – which consists of satirizing, criticizing some current social fact – and perception of the immediate interdiscourses implied in the text. Therefore, we understand that one of the strategies of reading is the observation of the figures networks and the themes to which they refer, this being one of the ways to establish the necessary connections between text-world, text-text and other text -discourses needed to understand cartoons.